Intrepid explorer : the autobiography of the world's best mine-finder - Lowell, J. David, 1928- (Sentinel Peak Books : University of Arizona Press, 2014)
"Intrepid Explorer is the story of the legendary career of the engineer, geologist, explorer, and international businessman J. David Lowell, whose life is recounted in his own words"--